The Concomitant Presence of Two Anomalous Muscles in the Forearm - Ogun, Tunç Cevat (Springer-Verlag, 2007)
This article describes the concomitant presence of two anomalous forearm muscles in a 20-year-old man, discovered accidentally during an operation for a forearm injury. The first one was similar to a reverse palmaris longus muscle except for its direction to the Guyon’s canal. The second one originated from the radial antebrachial fascia, superficial to all other forearm muscles in the lower half of the forearm, then diverged medially and extended into the Guyon’s canal and was innervated by the ulnar nerve. The patient had no symptoms related to overcrowding of the Guyon’s canal before the injury. A hand surgeon should be well informed about the anatomic variations of the hand to be comfortable during surgical practice.